2018
DOI: 10.1088/1612-202x/aae13b
|View full text |Cite
|
Sign up to set email alerts
|

In2Se3 saturable absorber for generating tunable Q-switched outputs from a bismuth–erbium doped fiber laser

Abstract: An Indium–selenide based saturable absorber is proposed and demonstrated for the passive generation of Q-switched pulses in a C- to L-band fiber laser. The proposed laser uses a 21 cm long bismuth–erbium doped fiber (Bi-EDF) as the linear gain medium, and is capable of generating passively Q-switched outputs that can be tuned over a bandwidth of 40 nm from 1533 nm to 1573 nm. The generated pulses have a maximum repetition rate of 52 kHz and a minimum pulse width of 2.2 μs at the maximum available pump power of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(39 reference statements)
2
5
1
Order By: Relevance
“…While the work by Ahmad et al (Ahmad et al 2016b) was able to generate outputs with a higher maximum repetition rate as well as higher maximum pulse energy, the system proposed in this work was able to generate output pulses with a smaller minimum pulse width that could be tuned along the C-band region. On the other hand, the SAs based on graphene (Wang et al 2012) and In2Se3 (Ahmad et al 2018c) were only able to generate output pulses with a lower maximum repetition rate and larger minimum pulse width as compared to our reported output pulses. Previous work using the WSSe based SA (Ahmad et al 2018b), reported a comparable maximum repetition rate and tuning range with that of this work as well.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…While the work by Ahmad et al (Ahmad et al 2016b) was able to generate outputs with a higher maximum repetition rate as well as higher maximum pulse energy, the system proposed in this work was able to generate output pulses with a smaller minimum pulse width that could be tuned along the C-band region. On the other hand, the SAs based on graphene (Wang et al 2012) and In2Se3 (Ahmad et al 2018c) were only able to generate output pulses with a lower maximum repetition rate and larger minimum pulse width as compared to our reported output pulses. Previous work using the WSSe based SA (Ahmad et al 2018b), reported a comparable maximum repetition rate and tuning range with that of this work as well.…”
Section: Resultscontrasting
confidence: 83%
“…In this regard, the strong intracavity lasing at high output powers will hasten the bleaching process of the Cu2Te SA, resulting in a higher repetition rate (Wood,Schwarz 1967). 1, the repetition rate of the proposed system was comparable to that of other similar works (Wang et al 2012;Ahmad et al 2018c;Ahmad et al 2018b). While the work by Ahmad et al (Ahmad et al 2016b) was able to generate outputs with a higher maximum repetition rate as well as higher maximum pulse energy, the system proposed in this work was able to generate output pulses with a smaller minimum pulse width that could be tuned along the C-band region.…”
Section: Resultssupporting
confidence: 58%
“…Table 1 summarizes performances of reported works that deal with various SA. As tabulated in Table 1, the repetition rate of the proposed system was comparable to that of other similar works (Wang et al 2012;Ahmad et al 2018c;Ahmad et al 2018b). While the work by Ahmad et al (Ahmad et al 2016b) was able to generate outputs with a higher maximum repetition rate as well as higher maximum pulse energy, the system proposed in this work was able to generate output pulses with a smaller minimum pulse width that could be tuned along the C-band region.…”
Section: Resultssupporting
confidence: 73%
“…Reliable, ultrafast fiber lasers are one of the most sought-after applications due to the advantages of their miniaturization, compact structure, and high reliability [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Among them, large-energy mode-locked fiber lasers have attracted more and more attention due to their indispensable applications in industrial material processing, medical treatment, scientific research, and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the traditional semiconductor saturable absorber mirrors (SESAMs), two-dimensional (2D) materials [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], quantum dots [ 28 , 29 ], metal nanoparticles [ 30 , 31 , 32 , 33 ], and other new SAs have been intensively studied. Furthermore, after graphene was found to have saturable absorption properties and used as SA for mode-locked lasers in 2009 [ 34 ], a wide range of 2D materials such as transition metal dichalcogenides (TMDs) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], topological insulators (TIs) [ 19 , 20 , 21 , 22 ], black phosphorus (BP) [ 23 , 24 ], MXenes [ 25 , 26 , 27 ], were shown to have great potential in the construction of high-performance and new functional optoelectronic devices [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ,…”
Section: Introductionmentioning
confidence: 99%